Caracterização e correlação física e química dos frutos de cultivares de mangueira em São Manuel, São Paulo - Silva, Andréa Carvalho da; Souza, Adilson Pacheco de; Leonel, Sarita [UNESP]; Souza, Manoel Euzébio de [UNESP]; Tanaka, Adriana Aki [UNESP] (My University, 2012)
In Brazil, mango production has great growth potential for different forms of consumption, but needs improvement in post-harvest techniques that enable the production of fruits with high quality and good ratios between physical and chemical properties. Therefore, the physical and physico-chemical characteristics of mango fruits of the Bourbon, Haden, Palmer, Tommy Atkins and Parwin cultivars were evaluated at the same maturity stage, in São Manuel, SP, by the following characteristics: fresh mass, longitudinal diameter (the apex of the stem) and transversal diameter (the shoulder fruit) medium, texture, pH, acidity, soluble solids, carbohydrates (reducing sugars, total sugars and starch) and ascorbic acid. There were significant differences between cultivars, with fresh mass varying from 431,0 g (‘Haden’) to 562,4 g (‘Palmer’), longitudinal diameter from 9,33 cm (‘Haden’) to 13,67 cm (‘Palmer’) and transversal diameter from 7,25 cm ('Bourbon') to 8,93 cm ('Parwin'), and the texture ranged from 103,19 N ('Palmer') to 67,91 N (‘Haden’). The ‘Palmer’ fruits presented fresh attributes (562 g), firmness (103.19 N) and ascorbic acid (34.27 mg 100 mL-1) superior to the fruits of Tommy Atkins, Bourbon , Haden and Parwin, and higher levels of sweetness and starch were obtained by 'Haden' and 'Parwin', respectively Estimates of the physical and chemical properties can be performed by linear and polynomial regression, with better results for cultivars with smaller fruit diameter variation rates.

No Brasil, a produção de manga apresenta grande potencial de crescimento para diferentes formas de consumo, todavia necessita de melhorias nas técnicas pós-colheita que propiciem a obtenção de frutos de alta qualidade e com boas relações entre as propriedades físico-químicas. Neste sentido, avaliaram-se as características físicas e químicas dos frutos das cultivares de mangueiras Bourbon, Haden, Palmer, Tommy Atkins e Parwin, no mesmo estádio de maturação, no município de São Manuel/SP, por meio de medidas da massa fresca, diâmetros longitudinal e transversal médios, textura, pH, acidez titulável, sólidos solúveis, carboidratos e ácido ascórbico. Verificaram-se diferenças significativas entre as cultivares, com massa fresca variando de 431,0 g (‘Haden’) a 562,4 g (‘Palmer’); diâmetro longitudinal de 9,33 cm (‘Haden’) a 13,67 cm (‘Palmer’) e transversal de 7,25 cm (‘Bourbon’) a 8,93 cm (‘Parwin’); e textura entre 67,91N (‘Haden’) a 103,19N (‘Palmer’). Das cultivares estudadas, os frutos de ‘Palmer’ apresentaram os atributos massa fresca (562 g), firmeza de polpa (103,19N) e teor de ácido ascórbico (34,27 mg 100mL-1) superiores aos frutos das cultivares Tommy Atkins, Bourbon, Haden e Parwin. Os maiores níveis de doçura e de amido foram obtidos por ‘Haden’ e ‘Parwin’, respectivamente, As estimativas das propriedades físicas e químicas podem ser realizadas por regressões lineares e polinomiais, com melhores resultados para cultivares com frutos com menor variação de razões diamêtricas.
Characterization and physical and chemical correlation of mango fruit cultivars in São Manuel, SP
Keywords: Mangifera indica L.; Post-harvest; Fruit quality; Nutritive value; Mangifera indica L.; Pós-colheita; Qualidade de fruto; Valor nutritivo